Internet Of Thing Based COVID Testing Booth - Mohapatra, Badri Narayan; Bhoje, Manisha; Patil, Labhesh; Dudhamal, Nitesh (LPPM Universitas Andalas, 2025)
In view of current situation the COVID-19 has become ubiquitous in every corner of the world. Every individual need to be cautious to overcome the spread of the COVID-19. It has become necessary to predict the COVID symptoms in order to allow the people at the public places and the entrances. The early symptoms of COVID-19 is high body temperature and change in pulses. It would be difficult to check temperature and take pulses of everyone, there might be a chance of being in contact with the person which is harmful. An automatic temperature scanning gate is presented to verify the body temperature and check pulses of any intruder. The main objective of the system is to monitor the human body temperature and take pulses when needed. In normal situation the gate is closed. If the module senses any high temperature (more than 37 degree Celsius) or the pulses are irregular, buzzer is activated indicating the detection of COVID symptom. Otherwise, the gate is opened, thus allowing the person into the room. The LCD displays the persons temperature and heart rate, being detected by sensor. In this project an attempt will be made to develop a prototype for covid testing booth for COVID 19 safety.